Effect of sago and tapioca starches on the physicochemical and textural properties of expanded rice product coloured with red beetroot (Beta vulgaris) powder - Abdul Alam, N. A.; Karim, Roselina; Syed Muhammad, Sharifah Kharidah (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2018)
Colour plays an important role in food especially in increasing the aesthetic value of food products. However, the increasing awareness on health implications of synthetic colourants has led to increased market for natural colourants. In this study, the retention of colourant from red beetroot powder in extruded rice flour containing 20% sago or tapioca starch was investigated. The moisture content of the rice flour-starch blends and 100% rice flour (control) was adjusted to 10% and the samples were extruded at 80ºC - 160ºC, with 120 rpm screw speed and 40 rpm feeder speed. The expansion, density, water absorption index (WAI), water solubility index (WSI), hardness, crispness, colour, and betanin content of the extrudates were measured. The results showed that rice flour-sago starch extrudates (RSE) and rice flour-tapioca starch extrudate (RTE) had better expansion compared to the control (100% rice flour) extrudate. The expansion of RTE was not significantly different from that of RSE and no significant difference was found in the densities of these two extrudates. Presence of sago or tapioca starch decreased the WAI and increased the WSI of the extrudates. The WAI of RSE, however, did not differ significantly from that of RTE. The hardness (18.37 kg) and crispness (126.55 kg.sec) of the control extrudate were higher than that of the RSE (16.97 kg, 110.07 kg.sec) and RTE (14.84 kg, 92.77 kg.sec). There was no significant difference between the redness values of the extrudates. However, retention of betanin in the extrudates was highest in RTE (36.06% retention), followed by RSE (34.14%) and lowest in the control extrudate (27.82%). Addition of tapioca starch or sago starch can help to improve the physical and textural properties of betanin coloured rice extrudates with tapioca starch giving higher betanin retention.